AS-SUNNAH SEBAGAI SUMBER HUKUM ISLAM: REFLEKSI TERHADAP HERMENEUTIKA MUHAMMAD SYAHRUR - Muhazir, Muhazir (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2018)
In recent years many studies have developed from both groups who doubt the authenticity of the Sunnah and the power of Sunnah as a source of Islamic law. This problem inspires Muslim scholars who consider that the group's doubts are due to the weakness of the study and the approach taken by the previous ulama as well as academic re-examination, the shahrur is a figure of Muslim scholars seeking hermeneutical methods so that the hadith still has original value and is accountable for academic value.